Load Frequency Control of an Isolated Power System in Presence of Controllable Energy Storage Devices - Mallareddy Mounica; Chinta Prasad; D. J. V Prasad; M. Aruna Bharathi (Majlesi Journal of Electrical Engineering)
The usage of energy storage units in power system will reduce frequency oscillations immediately subjected to random load changes. In this project, investigations are carried out for an isolated power system with ALFC unit and isolated power system with mutual coupling effects. In each case the effect of different storage units are studied for random load changes. Here particle swarm optimization algorithm (PSO) and improved particle swarm optimization technique (IPSO) are used to tune the parameters of storage units to provide proper control strategy for the system. Instead of using two flexible storage devices, here one flexible storage unit is considered with constant storage system.  Results are carried out in MATLAB/SIMULINK software.